Peterson’s Algorithm total correctness proof in IPCL - Zhygallo, A.A. (Проблеми програмування, 2016)
Доведено тотальну коректність алгоритму Пітерсона. За програмою зафіксовано стани та переходи транзиційної системи. Середо-вище виконання – паралельне з почерговим переключенням зі спільною пам’яттю. Сформульовано інваріант. Судження проведено в рамках методу доведення властивостей програм в Interleaving Parallel Compositional Languages (IPCL). Спираючись на дану та інші роботи автора зроблено висновки щодо адекватності застосування методу для подібних задач завдяки гнучкості композиційно-номінативної платформи та його практичності і легкості застосування для реальних систем. Доказана тотальная корректность алгоритма Петерсона. За программой зафиксированы состояния и переходы транзиционной системы. Среда выполнения – параллельная с поочередным переключением с общей памятью. Сформулировано инвариант. Суждение происходит в рамках метода доказательства свойств программ в Interleaving Parallel Compositional Languages (IPCL). Руководствуясь этой и другими работами автора сделано вывод об адекватности использования метода для подобных задач исходя из гибкости композиционно-номинативной платформы и его практичности и легкости в использовании для реальных систем. The total correctness of the Peterson’s Algorithm has been proved. States and transitions were fixed by the program. Runtime environment considered is interleaving concurrency with shared memory. Invariant of the program was constructed. All reasoning provided in terms of Method for software properties proof in Interleaving Parallel Compositional Languages (IPCL). Conclusions about adequacy of the Method usage for such a kind of tasks (thanks to flexibility of composition-nominative platform) and its practicality as well as ease of use for real-world systems have been made based on this and other author’s works.